Acid selective pro-dye for cellular compartments - Barbara Czaplińska (Scientific Reports, 2019)
Abstract A novel pro-dye approach for the acid-selective staining of the subcellular compartments for better permeability and selectivity was applied. The designed sensor has suitable physicochemical properties such as a large Stokes shift and a long-lived intracellular fluorescence. The Schiff base fragment was used for the acid-sensitive release of a fluorophore without affecting the overall stability of the biological systems. Due to the presence of an imine bond in its structure and its unique fluorescent properties, it can be presented as a “pro-dye” for acidic structures such as lysosomes. As a result of an imine bond cleavage, a new fluorescent compound is released, whose substantially shifted excitation and emission wavelengths enable a more selective and effective imaging of lysosomes and endosomes. The presented report provides the chemical, physicochemical and optical profiles as well as biological assays and theoretical calculations.